2021
DOI: 10.1111/ijac.13674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe3+ substitution on the structural modification and band structure modulated UV absorption of hydroxyapatite

Abstract: The effect of Fe3+ ionic substitution in hydroxyapatite (Ca10‐xFex(PO4)6(OH)2) was studied using structural modifications, resulting in an improvement in UV absorption through a tailored optical band structure. Ca2+ of HA being larger compared to Fe3+ contributes to the shrinkage of the lattice. Undoped HA has a peak at 1085 cm−1 (ʋ3 PO43−) which is shifted to 1033 cm−1 for Fe‐HA, because of the perturbation in HA structure. An improvement of UV absorption in the entire UVA and UVB range with an increase in Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The Raman spectrum of HA, illuminated the bands identified at 430, 489, 582, 593, 964 and 1047 cm −1 which were related to the various stretching and bending modes of the phosphates groups figure 6(a). In detail, P-O active modes were observed as follows; the PO 4 3− ν 2 vibrations appeared at 430 and 489 cm −1 [45][46][47]. The bands at 582 and 593 cm −1 were associated with PO 4…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Raman spectrum of HA, illuminated the bands identified at 430, 489, 582, 593, 964 and 1047 cm −1 which were related to the various stretching and bending modes of the phosphates groups figure 6(a). In detail, P-O active modes were observed as follows; the PO 4 3− ν 2 vibrations appeared at 430 and 489 cm −1 [45][46][47]. The bands at 582 and 593 cm −1 were associated with PO 4…”
Section: Resultsmentioning
confidence: 96%
“…3− ν 4 vibrations bending modes [45,47] and PO 4 3− ν 1 vibrations located at 964 cm −1 [11,[45][46][47][48], while the triply degenerated asymmetric stretching mode ν 3 of PO 4…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, HA has been proposed as a safe sunscreen ingredient, and the interest in CaPs for this application is growing [195,196]. In the literature, there are several examples that report the preparation of HA as a safe inorganic sunscreen ingredient to replace ZnO and TiO 2 [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211]. Indeed, it was found that HA shows not only non-toxicity and biocompatibility properties, but also screening capability, high dermal tolerance, and a lower whitening effect than other inorganic sunscreen agents.…”
Section: Skin Protection-sunscreen (Uv Protection)mentioning
confidence: 99%
“…An example is Fe 3+ that is largely used as dopant in HA and, as other elements, it could lead to an HA lattice contraction or extension depending on the iron concentration and on the mechanism of iron insertion [214,215]. In addition, as a result of the exchange between Fe 3+ and Ca 2+ the Ca/P ratio decreases showing the formation of a calcium-deficient HA [201]. The addition of Fe in HA improves the optical properties of the material; in particular, it shows a higher UV absorption over the whole UV range [202][203][204].…”
Section: Synthetic Calcium Phosphates As Sunscreensmentioning
confidence: 99%
“…In this study HAp can synthesis from iron, calcium and phosphate source precursors and urea. Fe is considered as a dopant in HAp, because it is, potentially less toxic than other transition metals [25]. HAp has an ability to inhibit the growth of bacterial activity.…”
Section: Introductionmentioning
confidence: 99%